“No patient should die of PPH just for the lack of training!” Experiences from multi-professional simulation training on postpartum hemorrhage in northern Tanzania: a qualitative study - Signe Egenberg; Bjørg Karlsen; Deodatus Massay; Happiness Kimaro; Lars Edvin Bru (BMC Medical Education, 2017)
Abstract Background Postpartum hemorrhage (PPH) is a major cause of maternal morbidity and mortality. In Tanzania, PPH causes 25% of maternal deaths. Skilled attendance is crucial to saving the lives of mothers and their newborns during childbirth. This study is a follow-up after multi-professional simulation training on PPH in northern Tanzania. The purpose was to enhance understanding and gain knowledge of important learning features and outcomes related to multi-professional simulation training on PPH. Methods The study had a descriptive and exploratory design. After the second annual simulation training at two hospitals in northern Tanzania, ten focus group discussions comprising 42 nurse midwives, doctors, and medical attendants, were carried out. A semi-structured interview guide was used during the discussions, which were audio-taped for qualitative content analysis of manifest content. Results The most important findings from the focus group discussions were the importance of team training as learning feature, and the perception of improved ability to use a teamwork approach to PPH. Regardless of profession and job tasks, the informants expressed enhanced self-efficacy and reduced perception of stress. The informants perceived that improved competence enabled them to provide efficient PPH management for improved maternal health. They recommended simulation training to be continued and disseminated. Conclusion Learning features, such as training in teams, skills training, and realistic repeated scenarios with consecutive debriefing for reflective learning, including a systems approach to human error, were crucial for enhanced teamwork. Informants’ confidence levels increased, their stress levels decreased, and they were confident that they offered better maternal services after training.